KISM Food & Markets: Knowledge Platform for Inclusive and Sustainable Food Markets and Value Chains - CGIAR Initiative on Rethinking Food Markets (2022)
No dedicated knowledge platform focused on both the inclusiveness and sustainability of food value chains is currently available. Hence, responding to these two needs, this Work Package 4 under the CGIAR research initiative Rethinking food markets established a Knowledge Platform for Inclusive and Sustainable Food Markets and Value Chains (KISM) to help farmer organizations, food businesses, governments, and practitioners make better-informed investment and policy decisions on inclusive and sustainable food value chains. KISM allows stakeholders to work with researchers and share research and best practices on bundling and scaling market interventions. Through the platform, new evidence generated by the Initiative will be collected and disseminated along with systematic reviews (meta studies) of existing case studies and impact assessments, and market and policy environment analyses on effectiveness and scalability of interventions. This evidence will be made ready for decision-making through (a) research syntheses; (b) guidelines on the adaptation and implementation of credible and innovative practices for market-based inclusive and sustainable business and value chain organization models; (c) policy dialogue; and (d) convening of partners and other stakeholder networks.